2008
DOI: 10.1128/aem.02080-07
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for Oxidation of High-Molecular-Weight Substrates by a Fungal Versatile Peroxidase, MnP2

Abstract: Unlike general peroxidases, Pleurotus ostreatus MnP2 was reported to have a unique property of direct oxidization of high-molecular-weight compounds, such as Poly R-478 and RNase A. To elucidate the mechanism for oxidation of polymeric substrates by MnP2, a series of mutant enzymes were produced by using a homologous gene expression system, and their reactivities were characterized. A mutant enzyme with an Ala substituting for an exposing Trp (W170A) drastically lost oxidation activity for veratryl alcohol (VA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…The laccase [16] and MnP [25] play a major role in complete oxidation of DB14. It was observed that laccase and peroxidases can act as starters of a chain reaction which leads to dye degradation by generating highly active free radicals (e.g., Mn 3+ , lipid, hydroxyl, and peroxy-radicals) [26, 27].…”
Section: Resultsmentioning
confidence: 99%
“…The laccase [16] and MnP [25] play a major role in complete oxidation of DB14. It was observed that laccase and peroxidases can act as starters of a chain reaction which leads to dye degradation by generating highly active free radicals (e.g., Mn 3+ , lipid, hydroxyl, and peroxy-radicals) [26, 27].…”
Section: Resultsmentioning
confidence: 99%
“…VP shares with manganese peroxidase and lignin peroxidase the ability to oxidize Mn(II) and high redox potential aromatic compounds, respectively (Tsukihara et al 2008;Ruiz-Dueñas et al 2009). This results suggest that the dye substrate interacts with a different enzyme active site that do not compete with Mn(II).…”
Section: Resultsmentioning
confidence: 99%
“…Homologous expression of several lignin degrading peroxidases has been reported in some fungi, especially P. chrysosporium 31,32) and Pleurotus ostreatus. 33,41) This expression system can be used to investigate the structure and function these enzymes, especially high oxidation activities against lignin model compounds, by site-directed mutagenesis. Moreover, molecular breeding of the superior lignin degrading fungi applied in the pretreatment of wood in the production of bio-ethanol is possible using this homologous expression system, since P. sordida YK-624 degrades lignin more effectively and selectively than P. chrysosporium or T. versicolor.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] In our previous report, a gene transformation system for P. sordida YK-624 was constructed, and expression of the enhanced green fluorescent protein (EGFP) was successful. 34) Development of a homologous gene expression system for this fungus is important to elucidate the reason it shows high lignin-degrading activity and selectivity.…”
mentioning
confidence: 99%